2012
DOI: 10.1016/j.cell.2012.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Direct Reprogramming of Mature Amniotic Cells into Endothelial Cells by ETS Factors and TGFβ Suppression

Abstract: ETS transcription factors ETV2, FLI1 and ERG1 specify pluripotent stem cells into endothelial cells (ECs). However, these ECs are unstable and drift towards non-vascular cell fates. We show that human mid-gestation c-Kit− lineage-committed amniotic cells (ACs) can be readily reprogrammed into induced vascular endothelial cells (iVECs). Transient ETV2 expression in ACs generated proliferative but immature iVECs, while co-expression with FLI1/ERG1 endowed iVECs with a vascular repertoire and morphology matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
213
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(228 citation statements)
references
References 46 publications
(51 reference statements)
13
213
2
Order By: Relevance
“…It is increasingly clear that obtaining ESC-derived cells with clinical quality by existing methods is a difficult task. Based on the same principle and methodology for iPSC reprogramming, a recent study demonstrated that forced expression of three transfection factors (Etv2, Fli1, and Erg1) that control vascular differentiation effectively converted hESCs to endothelial cells with significantly increased yield and maturity [23,45]. This study demonstrates that intervention at the transcriptional level can provide a strong internal driving force for cell-specific differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is increasingly clear that obtaining ESC-derived cells with clinical quality by existing methods is a difficult task. Based on the same principle and methodology for iPSC reprogramming, a recent study demonstrated that forced expression of three transfection factors (Etv2, Fli1, and Erg1) that control vascular differentiation effectively converted hESCs to endothelial cells with significantly increased yield and maturity [23,45]. This study demonstrates that intervention at the transcriptional level can provide a strong internal driving force for cell-specific differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that intervention at the transcriptional level can provide a strong internal driving force for cell-specific differentiation. However, the expression of the aforementioned transcription factors in that study was also mediated by viral vectors [23]. Using synthetic mRNA as an alternative gene expression approach could avoid the safety concerns associated with viral vectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2000, several transcription factors were discovered and were successfully used to reprogram target cells such as pancreatic islet cells (Zhou et al, 2008), neurons (Fishman et al, 2015;Vierbuchen et al, 2010), hepatocytes (Huang et al, 2011;Sekiya and Suzuki, 2011), endothelial cells (Ginsberg et al, 2012;Han et al, 2014), smooth muscle cells (Karamariti et al, 2013), and hepatocyte like cells (Simeonov and Uppal, 2014).…”
Section: Direct Reprogrammingmentioning
confidence: 99%